Automotive ergonomics driver-vehicle interaction - Gkikas, Nikolaos (Boca Raton, FL CRC Press, 2013)
"The name of Karl Benz, one of the father figures in the automotive industry, is quoted more than once in this book. This is not only because of his undoubted contribution during the initial phase of developments, but also because of the contrast of expectations by key figures such as himself against the established beliefs and practices of today. Common perception of what the automobile is and whom it is addressed to was significantly different back then. From the very few who could afford and the handful of those skilled enough to control such machines, within a few decades we were led to the generalization of the automobile, first in the US, then in Europe and post-WWII Japan"-- |c Provided by publisher.
Keywords: Automobiles -- Design and construction; Design -- Human factors; Automobile driving -- Physiological aspects; Human-computer interaction